한방입욕제(형개수) 사용을 통한 소양증을 호소 소아청소년의 삶의 질 개선효과 - 정경식(Kyung Sik Jeong); 백영화(Young Hwa Baek); 유종향(Jong Hyang Yoo); 황만기(Man Ki Hwang); 최영진(Young Jin Choi); 김윤희(Yun Hee Kim); 이시우(Si Woo Lee) (동의생리병리학회지, 2018)
Pruritus is the most prominent symptom of atopic dermatitis and other skin diseases. It is not easily improved and is a major factor that threatens the quality of life of patients and their families. The purpose of this study was to evaluate the effect of HyungGae-Water, which was bath preparation made from Korean medicine herbs, for children and adolescents suffering pruritus. The participants were 50 boys and girls aged from 2 to 15 years old. The HyungGae-Water was used once a day for 6 weeks, and we were followed up three times every two weeks. Of 50 participants enrolled, 47 completed the study. The outcome variables were dermatology quality of life scales in children, pruritus VAS, and investigator global assessment (IGA). The results of the study show that the dermatology quality of life is significantly improved and the VAS of pruritus has meaningful changes. In the IGA, moderate or severe improvement was observed in 48.9% and slight improvement in 17%. There were seven suspected or less relevant adverse events using HyungGae-Water. The present results suggest that the HyungGae-Water has alleviating effect for the pruritus in children and adolescents.